Impacts of wild boars on local livelihoods in rural communities: A case study of mountainous areas in southeast China - Wang, Chengchao; Zeng, Benxiang; Song, Xianqiang; Luo, Dongshen; Lin, Tingting (Frontiers in Environmental Science, 2023)
Wild boar (Sus scrofa) seriously threatens agricultural production and rural livelihoods worldwide. Human-wild boar conflict has become an important research topic. We investigated the impact of wild boars on local livelihoods and rural community’s responses to the impact, based on a case study in Fu’an City, Fujian Province, China. We conducted a questionnaire survey of 152 rural households in six villages of Fu’an City. Results demonstrated that the overall impact of wild boars on livelihoods was significant; however, there was household heterogeneity. The impact lied on the scale of agricultural output value and the extent of livelihood dependency on susceptible crops. Different impacts resulted in discrepant countermeasures of rural households in dealing with wild boars. The magnitude of economic losses caused by wild boars to a great extent determined the selection of prevention measures. Rural households with more economic losses tend to adopt costly and effective prevention measures, such as fencing and human guarding. Recommendations were put forward to address the human-wild boar conflicts.